Network pharmacology, experimental validation and pharmacokinetics integrated strategy to reveal pharmacological mechanism of goutengsan on methamphetamine dependence - Li, Han-Cheng; Li, Jie-Yu; Wang, Xing-Chen; Zeng, Ming; Wu, Yang-Kai; Chen, Yi-Ling; Kong, Cai-Hua; Chen, Ke-Lin; Wu, Jie-Ru; Mo, Zhi-Xian; Zhang, Jia-Xuan; Liu, Chang-Shun (Frontiers in Pharmacology, 2024)
Background: Goutengsan (GTS) is a traditional Chinese medicine formula that can improve multiple nervous system diseases, such as methamphetamine (MA) dependence. However, the mechanism how GTS treats MA dependence remains unclear. This study was aimed to investigate the action mechanism of GTS on MA dependence using network pharmacology, in vivo/ in vitro experimental validation, pharmacokinetics, and tissue distribution in the brain.The bioactive ingredients from GTS and possible targeted genes for treating MA dependence were predicted using network pharmacology. The binding of key components of GTS to the predicted proteins was studied using molecular docking, and the key components were verified by HPLC. The effects of GTS on an MA-induced model in rats and SH-SY5Y cells were studied. The regulatory effects of GTS on the expressions of predicted MAPK pathway-related proteins in rat brain tissues and SH-SY5Y cells were validated. Furthermore, the plasma exposure and brain tissue distribution of GTS ingredients for MA dependence treatment and MAPK pathway regulation were studied in mice.Results: Network pharmacology screened 53 active ingredients, and 287 potential targets of GTS, and showed the MAPK pathway was among the most relevant pathways. Molecular docking showed that key active ingredients (e.g., 6-gingerol, liquiritin and rhynchophylline) bound strongly with MAPK core targets, such as MAPK3, and MAPK8. Five compounds of GTS were detected by HPLC, including 6-gingerol, chlorogenic acid, liquiritin, 5-o-methylviscumaboloside and hesperidin.GTS had a therapeutic effect on MA-dependent rats, and reduced hippocampal CA1 damage and relative expressions of p-MAPK3/MAPK3, p-MAPK8/MAPK8 in brain tissues induced by MA. GTS counteracted aberrant alterations in cAMP, 5-TH and cellular morphology induced by MA induction and exerts therapeutic effects on MA-induced SH-SY5Y cell models. GTS also can antagonize the high expressions of MAPK-related proteins in MA-induced SH-SY5Y cells. Pharmacokinetic experiment revealed the four ingredients of GTS (e.g., chlorogenic acid, 5-o-methylviscumaboloside, hesperidin and rhynchophylline) were exposed in the plasma and brain, which demonstrates its pharmacological effect on MA dependence. Conclusion: GTS treats MA dependence by regulating the MAPK pathway via multiple bioactive ingredients. The network pharmacology, experimental validation and pharmacokinetics integrated strategy is efficient in discovering the key pharmacological mechanism of herbal formulae.